Latin american repertoire for clarinet, viola and piano: Catalog with comment (2019)
This article aims to provide a contribution for the recognition of the new repertoire of Latin American chamber music for clarinet, viola and piano. The nature of this document is not intended to be musicological or theoretical, but rather, an existing repertoire organization for this ensemble. To this end, the main sources consulted were Latin American composers referenced in personal and institutional web pages, interviews via email and reference catalogs. A list of works was compiled, as well as a review of their aesthetics and the experiences of the composers. This work is expected to facilitate subsequent staging, recording and analysis of these new works in the field of academic music and on the world cultural scene.